Kinematic characteristics of throwing with the heavier hammer during the hammer throw: Consideration of its usage for resisted training - Hirose, K.; Ohyama Byun, K.; Fujii, H.; Aoki, K.; Ogata, M. (Japan Journal of Physical Education, Health and Sport Sciences, 2016)
The purpose of this study was to investigate the kinematics of the throw with the competition hammer (7.26 kg) and the heavier hammer (8.0 kg). Sixteen male hammer throwers threw hammers of both weights at maximum effort. Utilizing three high-speed video cameras (300 fps), three-dimensional coordinates of the hammer head and 25 landmarks on the body were obtained by the direct linear transformation method. Hammer head velocity and distance thrown with the heavier hammer were significantly lower than for the throw with the competition hammer. Durations of the turn and double support phase (DSP) in the throw with the heavier hammer were significantly longer than with the competition hammer. Focusing on changes in the velocity of the hammer head, the duration of acceleration with the heavier hammer during the 1st and 2nd turns was longer than for the competition hammer. The Y component of displacement of the center of gravity for the heavier hammer was longer in every phase than for the competition hammer. These results suggest that the throw with the heavier hammer can be an effective training method for acquiring a longer movement of the center of gravity toward the throwing direction during the DSP and longer acceleration of the hammer head.